Real-World Study on Implementation of Genomic Tests for Advanced Lung Adenocarcinoma in Brazil - Rodrigo Dienstmann; Leonard M. da Silva; Fernanda Orpinelli Ramos do Rego; Amanda Muniz Rodrigues; Fernanda Christtanini Koyama; Layla Testa Galindo; Carolina de Bustamante Fernandes; Bruno Batista de Souza; Rafael Duarte Paes; Tatiane Montella; Pedro de Marchi; Breno Jeha Araújo; et al. (JCO Global Oncology)
PURPOSETissue inadequacy and operational challenges may limit lung cancer comprehensive biomarker testing. Here, we describe the initial implementation of a tailored tissue molecular journey at Oncoclínicas Precision Medicine Laboratory in Brazil, which includes fast-track (FT) non–next-generation sequencing (NGS) assays combined with a broad NGS panel.METHODSFrom 2021 to 2023, all nonsquamous lung cancer samples eligible for the patient support program “Lung Mapping Consortium” at Oncoclínicas & Co were evaluated using the FT panel (immunohistochemistry for PD-L1 and anaplastic lymphoma kinase [ALK], polymerase chain reaction for EGFR and BRAF, and fluorescence in situ hybridization for ROS1) plus a broad DNA and RNA sequencing panel of 180 genes (custom ARCHER panel).RESULTSFrom 1,272 samples received by the laboratory, 3% had no tissue for any molecular testing, 20% was not eligible for broad NGS panel as per pathologist assessment (tumor purity and quantity), additional 12% did not reach presequencing analytical thresholds (nucleic acid quantity and/or quality), and 3% had postsequencing failure. Most frequent alterations were KRAS mutations (28.4%, KRASG12C 9.7%), EGFR mutations (23.6%, exon20 insertions 2.9%), ALK fusions (6.4%), MET exon 14 skipping (4.4%), ERBB2 mutations (3.4%), ROS1 fusions (3.1%), and BRAFV600E (1.9%). In 35% of the samples, FT non-NGS tests were the only molecular diagnostics: EGFR mutations (14%), ALK fusions (4.4%), ROS1 fusions (1.8%), and BRAFV600E (0.7%). Overall, high PD-L1 expression (≥50%) was found in 12.3%.CONCLUSIONThis study provides data on the molecular epidemiology of lung adenocarcinoma in Brazil, confirming high prevalence of EGFR mutations, ALK fusions, and MET exon 14 skipping alteration. Biomarker detection is largely affected by biospecimen collection and processing, with one third of the patients eligible for non-NGS testing only, which presents reduced coverage and sensitivity for actionable drivers.